2022
DOI: 10.3390/cancers14205073
|View full text |Cite
|
Sign up to set email alerts
|

Identification of EGFR-Related LINC00460/mir-338-3p/MCM4 Regulatory Axis as Diagnostic and Prognostic Biomarker of Lung Adenocarcinoma Based on Comprehensive Bioinformatics Analysis and Experimental Validation

Abstract: Background: Lung adenocarcinoma (LUAD) is one of the most aggressive and lethal tumor types and requires effective diagnostic and therapeutic targets. Though the epidermal growth factor receptor (EGFR) is an important target for LUAD therapy, acquired resistance is still inevitable. In recent years, the regulation of the EGFR by competing endogenous RNAs (ceRNAs) has been extensively studied and significant progress has been made. Therefore, we aim to find new targets for the diagnosis and treatment of LUAD by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…In UTUC, the overexpression of HER2 and EGFR are associated with a high tumor stage, high histological grade, and poor survival [5]. Interestingly, a recent study has demonstrated that a relationship between EGFR and MCM4 is observed in lung adenocarcinoma [30]. In addition, our previous study has con rmed the MCM4 was associated with AKT, ERK and EGFR pathways by functional analysis using GC cell lines [13].…”
Section: Discussionmentioning
confidence: 95%
“…In UTUC, the overexpression of HER2 and EGFR are associated with a high tumor stage, high histological grade, and poor survival [5]. Interestingly, a recent study has demonstrated that a relationship between EGFR and MCM4 is observed in lung adenocarcinoma [30]. In addition, our previous study has con rmed the MCM4 was associated with AKT, ERK and EGFR pathways by functional analysis using GC cell lines [13].…”
Section: Discussionmentioning
confidence: 95%
“…There are three main ways in which lncRNAs regulate genes: epigenetic regulation, transcriptional and post-transcriptional regulation, and their biological function depends on their location in the cell ( Jia et al, 2022 ). In the nucleus, some lncRNAs can become histone modifiers through methylation or demethylation, thereby regulating the chromatin state and ultimately promoting or repressing gene transcription ( Herman et al, 2022 ).…”
Section: Classification and Molecular Biological Functions Of Lncrnamentioning
confidence: 99%
“…The MCM3 gene is essential for the initiation of DNA replication and is involved in ensuring the precise initiation of DNA replication once per cell cycle 9 . The MCM4 gene is mainly enriched in the cell cycle and cell division and is also significantly associated with tumor size and, lymph node metastasis 10 . The MCM5 gene is associated with malignant status and poor prognosis in cervical adenocarcinoma patients, modulates cervical adenocarcinoma cells proliferation, inhibits the cell cycle and promotes colorectal cancer cells in vitro 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%